How to Develop Rubrics – A Step-by-Step Guide - Sridevi, K . V. Sridevi (THE PRIMARY TEACHER, 2018)
This paper describes the need and importance of self-assessment in school education. We all know that the focus of learning and assessment of children must include different skills, concerns, values, dispositions and sensitivities besides knowledge. In this context Rubrics as efficient tools for teacher assessment, self-assessment and peer-assessment are presented in this paper. Further, this paper also describes the development of Rubrics step-by-step with illustrations. It also elaborates the use of rubrics in bringing transparency and objectivity in assessment; developing preparedness and responsibility among learners and helping teachers to identify gaps and weaknesses in students' understanding.